Achieving growth through social innovation: a beyond GDP trial. Case studies of Turkey and Russia - Chiklyaukova, Ekaterina. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
Beyond GDP approach emphasizes that GDP alone is not comprehensive enough to capture the factors that contribute to the growth in the society. For several years, academicians try to identify the perfect indicator, which describes state of our well-being in the best way. The thesis’ novelty is in its aim of identification of the conceptual relationship between Beyond GDP and social innovation by analyzing the ecosystem of social innovation. There are three major aims defined. The first one is to identify the potential of “beyond GDP” on social innovation. The second one is to propose a novel approach to defining social innovation ecosystem in the light of Social Progress Index, Global Innovation Index and the Legatum Prosperity Index. Volunteering was added to the ecosystem as a unique enabler of social innovation. The development of optimal social innovation ecosystem is to be followed by the specific ones for Turkey and Russia, based on the analysis of respective index indicators scores. The third one is to conduct a case study of social innovation initiatives in Turkey and Russia. Two examples of local foundations that operate with a help of volunteers were examined. At the end of the thesis, policy making recommendations based on the best practices are provided.
Keywords: Social change -- Turkey.; Social change -- Russia (Federation)